Miejsce spółdzielczości w systemie społeczno-gospodarczym Polski i szanse jej rozwoju - Mierzwa, Danuta (The Place of Cooperative Movement in the Social-Economic System in Poland and Its Prospects of Development, 2006)
The cooperatives are considered to be an important part of the European market, despite great variety of structures of the economic entities. The agricultural cooperative movement - in which people organize themselves in order to accumulate resources indispensable in creating common productive and servicing potential - is very important. Yet it should undergo deep transformation and reconstruction, as cooperative entities play hardly any role, except for the dairy cooperatives. The cooperatives in European Union made these changes long ago and they are now considered to be an integral part of the market. They are a valuable bridge between the forces of globalization and local business activity.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 118-122